The effect of an 8-week vegan diet on the nutritional status and performance of semi-professional soccer players - results of the VegInSoc study - Nebl, J.; Bruns, P.; Meier, M.; Mayer, F.; Smollich, M.; Keller, M. (Nutrients, 2025)
Background/Objectives: Although there is an increasing interest among athletes in adopting plant-based diets, there is insufficient research available to determine how a vegan diet affects soccer performance. Methods: This interventional pilot study examined the effect of an 8-week vegan diet (VEG, n = 10) on nutritional status and athletic performance in semi-professional soccer players compared to controls (CON, n = 8). The study employed a controlled, non-randomized, longitudinal pilot study design during the season to compare the two groups. Results: Both groups displayed overall differences in nutrient intake, including insufficient energy and carbohydrates (t2: 46.2 [40.3-52.2] En% (VEG) vs. 37.6 [34.1-41.1] En% (CON); p = 0.036, Cohen`s d = 1.321). Notably, biochemical parameters 25(OH)D and ferritin levels fell within the normal ranges for both groups. The VEG group exhibited favorable changes in total and LDL cholesterol levels. Both groups had increased performances on the treadmill over the entire course of the study (VEG: +0.87 km/h (6.6%); CON: +0.96 km/h (7%); p > 0.05). The initial relative VO2max at t0 was comparable between the groups. Primarily due to the significant weight loss in the VEG group (-1.94 kg, p = 0.007) rather than a change in absolute VO2max values, we found an increased relative VO2max in the VEG group, which was significantly different from that of the CON group (57.0 [53.7-60.3] mL/kg/min (VEG) vs. 51.6 [48.1-55.0] mL/kg/min (CON); p = 0.041, Cohen`s d = 1.675). Conclusions: These findings suggest that a short-term vegan diet does not adversely affect training-induced performance improvements and may be suitable for semi-professional soccer players.